Ghost whisperer Season 1 Discs 1 & 2 - Hewitt, Jennifer Love, 1979-; Conrad, David, 1967-; Tyler, Aisha; Gray, John, 1958-; Paramount Pictures Corporation (Hollywood, Calif. : Paramount Pictures, 2006)
Ever since she was a young girl, Melinda Gordon has been able to see and talk to dead people. Earth-bound spirits who have yet to cross over to the other side seek her help in communicating and resolving unfinished business with the living.
Disc 1: Pilot -- The crossing -- Ghost, interrupted -- Mended hearts -- Disc 2: Lost boys -- Homecoming -- Hope and mercy -- On the wings of a dove.
Part 1 of 3.
Created by John Gray.
Originally broadcast on CBS television during the 2005-2006 season.
Special features: Cast & crew audio comentaries on select episodes; deleted scenes.
Jennifer Love Hewitt, David Conrad, Aisha Tyler.
Not rated.
Keywords: Mediums -- Drama; Ghost plays; Spirits -- Drama; Spiritualism -- Drama; Supernatural -- Drama; Businesswomen -- Drama; Spouses -- Drama; Drama; Fantasy television programs; Ghost television programs; Television programs; Television programs for the hearing impaired